Caso de estudio: análisis y diagnóstico de un policlínico familiar, propuesta de mejora - Soto Melo, Irene Emperatriz (2022)
The following professional proficiency project aims to analyse the business plan of JASMEDICA, a family-owned medical center, which focuses on paediatric medical care. The development is divided into four major chapters to assess the company's current situation and propose strategies that will lead the company to achieve its objectives. The first chapter covers the strategic diagnosis of the company, which is subdivided into two parts, the internal diagnosis, in which a brief explanation of the history of the company was made, the analysis of the business model, analysis of the value chain, definition of the competitive advantages and the determination of the strengths and weaknesses of the polyclinic, and the external diagnosis which was carried out through the PEST analysis, Porter's five forces, and the determination and support of opportunities and threats of the environment. Based on the information obtained, a strategy was formulated, for which the EFI and EFE matrix, the generic strategy matrix, the strategic position matrix and the evaluation of actions, and the development of the SWOT matrix were developed and utilized. Likewise, the institution's vision, mission, policies, and strategic objectives were defined that provide to JASMEDICA, the opportunity to grow and increase the share of market in the other hand, in the third chapter, the company's organizational structure was evaluated, and a proposal for changes was suggested to implement strategies. In the fourth chapter, strategic control was established through the design of a strategic control map in which the strategic objectives of JASMEDICA were included. The research work culminates with the conclusions and recommendations for the company.